Developmental toxicity of organotin compounds in animals - Wu, Lijiao; Chen, Zhenhuang; Zhu, Jingmin; Hu, Lingling; Huang, Xiao; Shi, Huahong (Frontiers in Marine Science, 2014)
Organotin compounds (OTs) have been used as biocides in antifouling paints and agriculture. The IMO introduced a global ban on the use of OTs in antifouling systems in 2001 due to their high toxicity. However, OTs have still been detected in the environment and pose a threat to the ecosystem. Several research groups have summarized the analytical methods, environmental fate, biochemistry, reproductive toxicity and mechanisms of actions of OTs. Here, we reviewed the developmental toxicity of OTs in various organisms such as sea urchin, ascidian, mussel and fish. The differences in sensitivity to OT exposure exist not only in different species but also at different stages in the same species. Though some hypotheses have been proposed to explain the developmental toxicity of OTs, the solid evidences are greatly in need.